A Flexible Exoskeleton Robot for Assisting Both Hip Joint Extension and Flexion - Youfu Liu; Jun Lu (Jixie chuandong)
With growing of lower limb exoskeleton robots， large variety of rigid exoskeletons are designed for medical rehabilitation and the other purposes. Compared with the rigid exoskeletons， which added extra inertial to low limb and restricted wearer movement， but the flexible wearable lower extremity exoskeleton minimizes the impact of these factors on the human body locomotion. An exoskeleton that provides assistive force for both hip joint extension and flexion is designed through the variation in hip joint dynamics during strides. Based on the change of hip joint moment， an assistance strategy desired force curve is proposed. In order to obtain the actual force acting on the hip joint， motor is controlled to track the desired force curve PD type iterative learning control （ILC） method is introduced to reduce the error caused by wearing position and biological characteristics to improve assistance performance. In order to evaluate assistance performance， the metabolism of four subjects wearing exoskeleton in the situations of that without assistance， assisting both hip extension and hip flexion， and assisting hip extension respectively is measured. The assistant effect is evaluated through the metabolism. Compared with assisting hip joint extension only and wearing exoskeleton with no assistance， results indicate that the decrease in average net metabolism of assisting both hip joint extension and flexion is 0.445 W/kg and 1.027 W/kg respectively， corresponding to the average net metabolism rate decrease is 7.45% and 15.67%.